Selection of Landfill Site in Khartoum State Using (GIS) Techniques and Multicriteria Decision Analysis (MCDA) - Abdul Azzez, Dr. Abdul Alraheem Alhag; Yosif, Dr. Yosif Ali; HUSSIENPH.D , FADWA A. (University of Thi-Qar Journal, 2019)
In this study, candidate sites for an appropriate landfill area of Khartoum are determined by using the integration of Geographic Information Systems (GIS) and multicriteria decision analysis (MCDA).Using these approaches leading to integrated environmental management are necessary to allow consideration of all components and processes in environmentGIS and environmental models function with a broad spectrum of geospatial data that are used for diverse applications and spatial analyses at different scales.Data are collected through observation, measurement, and inference.The examination and organization of data into a useful form produced information, whichthen enables appropriate analysis and modeling. for this purpose, input digital map layers including settlement (urban center, villages, and industrial areas), main roads , airports, wetlands, digital elevation model , land use (camps, palace, water and waste water treatment plants, agricultural zone, gardens and buildings ) and surface water ( streams and main irrigation channels ) are prepared and Weighted Overlaymethod are implemented to a geographical information system. It has focused on the formulation ofstandardsLandfill planning, and give it arranged for each standard and weighted , and then build a model and extract map representing more convenient for the establishment of landfill waste sitesto stay healthy waste dumps in the state of Khartoum ??????